High-rise green buildings in tropical countries - Wang, Meihong (2017)
In this modern world, with the depletion of natural resources, erratic climate change, energy crisis and loss of biodiversity, the emphasis on relieving the burden of Mother Natural have become prominent and actions for recourse are now inevitable. The global conversion rate of suburban into cities is frightening as the damages to the environment in the bid of higher quality of life had imposes almost irreversible damage already. The buildings have been a major consumer of energy; hence the importance of green building becomes vital.